2020
DOI: 10.5014/ajot.2020.74s1-po1410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Balance (OB) on Health, Quality of Life and Related Variables in Community-Dwelling Older Adults: Structural Equation Modeling

Abstract: Date Presented 03/26/20 The area of OT has been extended to preventive approaches from rehab. With regard to the increasing aging population, health professionals are trying to find effective approaches to maintaining and enhancing the health of healthy older adults. Although the concept of OB has a potential for preventive intervention, little is known about the scientific relationship between OB and health-related variables in older adults. Primary Author and Speaker: Sangmi Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The moderate relationship between OBQ11-A scores and FQOL-2006 global scores indicates good convergent validity. This finding is significant, and it adds evidence to the role of OB in quality of life (Park et al, 2020; Wagman et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The moderate relationship between OBQ11-A scores and FQOL-2006 global scores indicates good convergent validity. This finding is significant, and it adds evidence to the role of OB in quality of life (Park et al, 2020; Wagman et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…Occupational balance (OB) is one of the core concepts in occupational therapy (OT), and it has been found that quality of life can be improved by promoting it (Park et al, 2020). OB is related to quality of life, overall health and well-being, life satisfaction, and reduced stress levels (Håkansson et al, 2009; Håkansson and Ahlborg, 2016; Håkansson et al, 2020, 2021; Håkansson and Lexén, 2021; Wagman et al, 2019, 2020; Wagman and Håkansson, 2014a, 2014b; Wilcock et al, 1997; Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additional advantages of attaining occupational balance include reduced stress levels and heightened well-being or overall health (S. Park et al, 2021). Increased levels of occupational balance positively impact subjective health, quality of life, and healthrelated variables among relatively healthy older adults (S. Park et al, 2021). These findings endorse the importance of employing the notion of occupational balance to protect the health and quality of life of elderly individuals (S. Park et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 91%
“…In individuals over 65, maintaining a sense of equilibrium in their activities positively contributes to safeguarding their health (S. Park et al, 2021). Additional advantages of attaining occupational balance include reduced stress levels and heightened well-being or overall health (S. Park et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation